The Flood Protection Benefits and Restoration Costs for Mangroves in Jamaica - Ortega, Saul Torres; Losada, Inigo J.; Espejo, Antonio; Abad, Sheila; Narayan, Siddharth; Beck, Michael W. (World Bank, Washington, DC, 2021)
Jamaica, like other Caribbean and island nations is at high risk from coastal flooding and related hazards. Vulnerable coastal communities in Jamaica receive significant flood protection benefits from natural habitats like mangroves and coral reefs, even though these habitats are threatened by human development and activity and by natural stressors such as sea-level rise and climate change. As coastal flooding and habitat loss increase, there is great imperative among national disaster risk reduction agencies, conservation agencies and international aid institutions in Jamaica, to quantify the economic value of conserving and restoring mangrove habitats for risk reduction and to thereby inform national risk reduction, climate adaptation and conservation plans. This technical report provides an ecological, economic and social assessment of the habitat status, risks, costs and flood protection benefits of mangroves in Jamaica with a focus on their role in coastal flood risk reduction. This work aims to support decisions for sustainable and cost-effective approaches for mangrove management and flood risk reduction. First, authors assess the current status and recent trends in the distribution of mangroves in Jamaica. We then review the costs of restoration mangrove projects across Jamaica and the wider Caribbean. Using connected assessments, authors consider the nationwide restoration potential for mangroves. The authors then focus on a rigorous nationwide assessment of flood risk and the risk reduction benefits of mangroves to people and property across Jamaica.